Brazil : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Brazil. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that a mild recovery supported by accommodative monetary and fiscal policies is currently under way in Brazil. But the economy is underperforming relative to its potential, public debt is high and increasing, and, more importantly, medium-term growth prospects remain uninspiring, absent further reforms. Against the backdrop of tightening global financial conditions, placing Brazil on a path of strong, balanced and durable growth requires a committed pursuit of fiscal consolidation, ambitious structural reforms, and a strengthening of the financial sector architecture. Following the severe recession in 2015-16, real GDP grew by 1 percent in 2017. Growth is projected to be 1.8 and 2.5 percent in 2018 and 2019, respectively, driven by a recovery in domestic consumption and investment.